Effects of different feeding regimens on growth, longevity, and semen characteristics of working boars in a commercial AI stud - Sulabo, R.C.; Quackenbush, J.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The objective of the study was to determine the effects of 2 different feeding regimens on growth performance, semen production and quality, and longevity of boars in a commercial AI stud. A total of 30 replacement boars (PIC TR4, 375 lb and 14.2 mo of age) were randomly selected and allotted to 1 of 2 treatments. The control feeding program was the normal feeding program of the stud; boars were fed 6.7 lb/d for the first 8 wk, and then feeding was adjusted according to body condition of the individual boar. For the treatment feeding program, boars were fed 5.8 lb/d in the first 4 wk until boars reached 400 lb; afterward, boars were fed 6.0 lb/d for the duration of the study. Boars were weighed periodically to determine periodic and overall ADG. Semen was collected from each boar once a week for a total duration of 16 mo. Semen production and quality was determined for each ejaculate. Overall, treatment boars were consistently heavier than the control boars throughout the duration of the study because of their higher periodic and overall daily gains. At the end of the test, treatment boars were 32 lb heavier (P < 0.15) than the control boars. A higher proportion of treatment boars (73 vs. 42%) were active at the end of the study, which numerically increased (P > 0.35) average days in the stud (345 vs. 279 d), semen collections (58 vs. 49), and doses produced (1,238 vs. 1,077). There were no differences (P > 0.28) in the volume, sperm cell concentration, sperm cell count, and doses produced per ejaculate between boars fed the two feeding programs. Likewise, motility rates and proportion of normal cells in ejaculates were similar (P > 0.33) between boars fed the control and treatment feeding program. In conclusion, AI boars can be fed to a set feeding level to achieve targeted weight gains to influence longevity without affecting semen production and quality.
Keywords: Boars; Growth rate; Longevity; Semen characteristics